2023
DOI: 10.1111/acel.13976
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide riboside intervention alleviates hematopoietic system injury of ionizing radiation‐induced premature aging mice

Wenxuan Li,
Xinyue Wang,
Yinping Dong
et al.

Abstract: Radiotherapy destroys cancer cells and inevitably harms normal human tissues, causing delayed effects of acute radiation exposure (DEARE) and accelerating the aging process in most survivors. However, effective methods for preventing premature aging induced by ionizing radiation are lacking. In this study, the premature aging mice of DEARE model was established after 6 Gy total body irradiation (TBI). Then the therapeutic effects and mechanism of nicotinamide riboside on the premature aging mice were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Regardless of the inducing stimulus, senescent cells share common mechanisms for activation and maintenance of senescence, which are associated with p53, p21, p16, and pRB proteins [ 2 ]. Li et al [ 184 ] observed increased expression of p-p38, p38, and p16 INK4a proteins in the spleen of irradiated mice. Simultaneously, IR decreases the level of SIRT1, which represses the transcriptional activity of p53 by deacetylation [ 185 ], resulting in increased expression of p53 and p21 CIP1 .…”
Section: Radiation-induced Cellular Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the inducing stimulus, senescent cells share common mechanisms for activation and maintenance of senescence, which are associated with p53, p21, p16, and pRB proteins [ 2 ]. Li et al [ 184 ] observed increased expression of p-p38, p38, and p16 INK4a proteins in the spleen of irradiated mice. Simultaneously, IR decreases the level of SIRT1, which represses the transcriptional activity of p53 by deacetylation [ 185 ], resulting in increased expression of p53 and p21 CIP1 .…”
Section: Radiation-induced Cellular Senescencementioning
confidence: 99%
“…The dose response of γH2AX foci was analyzed 24 h, 96 h, 1 week, 2 weeks, and 4 weeks after irradiation Residual γH2AX foci persisted in human lymphocytes up to 4 weeks after irradiation [183] HUVECs X-rays 1 or 5 Gy Synchronized G0/G1 phase HUVECs were irradiated with an X-ray dose of 1 or 5 Gy and IRIF were studied from 10 min to 7 days after irradiation By 7 days after irradiation with 5 Gy, the mean number of γH2AX IRIF per nucleus was still significantly more than in unirradiated cells [182] Regardless of the inducing stimulus, senescent cells share common mechanisms for activation and maintenance of senescence, which are associated with p53, p21, p16, and pRB proteins [2]. Li et al [184] observed increased expression of p-p38, p38, and p16 INK4a proteins in the spleen of irradiated mice. Simultaneously, IR decreases the level of SIRT1, which represses the transcriptional activity of p53 by deacetylation [185], resulting in increased expression of p53 and p21 CIP1 .…”
Section: Neurons γ-Rays 5 Gymentioning
confidence: 99%